THE RELATIONSHIP BETWEEN WORKLOAD AND EDUCATOR STRESS - Dorris Yadewani; Reni Wijaya; Mustika Lukman Arief; Agus Nurofik (Bajang Institute, 2021)
The purpose of this study was to empirically examine the relationship between workload and work stress on educators. This research is an analytic study with a cross sectional approach. The population used in this study were all 31 Padang AMSS education staff in 2019. The sampling technique is using a saturated sample. Techniques for collecting data were field studies, namely observation and interviews and distributing questionnaires. The research variable consisted of 2 types, namely the independent variable in the form of workload, and the dependent variable in the form of work stress. The sampling technique was total sampling because the total population consisted of 31 educators and 1 leader. The research used survey techniques for descriptive studies using the SPSS version. 18.0. The instrument used is a questionnaire for workload and work stress variables with five Likert scales ranging from 1 to 5 (strongly disagree to strongly agree). Data was collected using a workload scale and a work stress scale. the results of research that have been carried out concluded that there is a significant relationship between workload and work stress for educators at AMSS Padang. This is indicated by the value of p = 0.00 (< 0.05), meaning that if the workload on employees increases, the stress level of employees will also increase so as to avoid various obstacles in serving the needs of the academic community, especially AMSS Padang students. For leaders, it is hoped that they will be able to provide continuous supervision in a clear division of work so that educators do not feel burdened with the tasks and responsibilities given so that stress at work can be minimized